Keeping them in their place: The ambivalent relationship between development and migration in Africa - Bakewell, O (Routledge, 2008)
While there has been an explosion of academic and practitioner interest in the relationship between migration and development in the past decade, this article poses the neglected question of what is meant by development in this literature. It focuses on the ideas of development underpinning development interventions across Africa and shows how they have sedentary roots which are focused on the control of mobility and tend to cast migration as a symptom of development failure. This can be seen in the ongoing ambivalence of many development actors towards migration across Africa. The article argues that the current initiatives to link migration and development will remain fundamentally flawed until the concept of development is reconceptualised for a mobile world. In particular, it calls for the reconsideration of the ideas of the good life envisaged in development initiatives, moving beyond models of development based on the nation-state and abandoning the paternalist paradigms that fail to recognise the agency of migrants from poor countries.